Microstructure of ferrite-martensite dual phase steels - Šiđanin, Leposava (Journal of Production Engineering, 1989)
This paper presents the results of dual-phase steel microstructures produced by different heat treatments. Three types of martensite morphologies were obtained. The character of the martensite, whether dislocated lath or twinned plate, was determined by transmission electron microscopy.